2011
DOI: 10.1002/mrm.22855
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative tracking of edema, hemorrhage, and microvascular obstruction in subacute myocardial infarction in a porcine model by MRI

Abstract: Pathophysiological responses after acute myocardial infarction include edema, hemorrhage, and microvascular obstruction along with cellular damage. The in vivo evolution of these processes simultaneously throughout infarct healing has not been well characterized. The purpose of our study was to quantitatively monitor the time course of these mechanisms by MRI in a porcine model of myocardial infarction. Ten pigs underwent MRI before coronary occlusion with subgroups studied at day 2 and weeks 1, 2, 4, and 6 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
108
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 45 publications
14
108
0
1
Order By: Relevance
“…So far, most observations on the time course of MO are available from short-term animal studies. Consistent with our data, Ghurge et al (14) found a resolution of MO and T2* abnormality after six weeks in a porcine model of myocardial infarction. Rochitte et al (2) found an increasing extent of MO and infarct size within the first 48 hours after ischemia in a study of seven dogs.…”
Section: Discussionsupporting
confidence: 93%
“…So far, most observations on the time course of MO are available from short-term animal studies. Consistent with our data, Ghurge et al (14) found a resolution of MO and T2* abnormality after six weeks in a porcine model of myocardial infarction. Rochitte et al (2) found an increasing extent of MO and infarct size within the first 48 hours after ischemia in a study of seven dogs.…”
Section: Discussionsupporting
confidence: 93%
“…MVO is the core of MI induced by ASA. 8,13,19 On LGE imaging, the signal intensity of MVO was higher than that of remote myocardium. This might be explained by the T 1 -shortening effect of some hemoglobin contents or by partial volume effect.…”
Section: Discussionmentioning
confidence: 99%
“…21 The ceSSFP imaging acquired 3 to 7 min after gadolinium injection may reflect an expanded interstitial space or hyperemia in addition to tissue edema. [11][12][13]16,22 These factors may have contributed to the feasibility of ceSSFP for visualizing both MI and MVO following ASA. On the other hand, we could visualize MI 11, 12 We used no preparation pulse, such as T 2 -preparation or black-blood pulse, 11,12 to improve visualization of myocardial edema on routine cine SSFP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microvascular obstruction was defined as a dark zone on early gadolinium enhancement imaging 1, 3, and 5 minutes postcontrast injection that remained present within an area of late gadolinium enhancement at 15 minutes. On the T2* CMR maps, a region of reduced signal intensity within the infarcted area, with a T2* value of <20 milliseconds17, 18, 19, 20 was considered to confirm the presence of myocardial hemorrhage.…”
Section: Methodsmentioning
confidence: 99%